Dynamics of financial development, innovation, trade, and economic growth: evidence from developed and developing nations - Kushwah, S.V.; Siddiqui, A.A.; Singh, P. (University of Jaffna, 2022)
The paper empirically explores the interrelationship among financial development, innovation, trade, and economic growth in 20 developing and developed nations. It applies the panel data methodology to give detailed and more efficient information about the study variables. Further to this, Principal component analysis is applied on the panel data to reduce the eighteen dimensions of financial development and six dimensions of innovation into two indices, separately for developed and developing nations. To bring out the best linkage possible between the stated variables, Panel regression is employed such as Dynamic OLS, Fully Modified OLS and Simple OLS. The study’s key finding indicates a significant relationship between economic growth (EG), trade (TO) and innovation for developed nations. A significant relationship exists between economic growth (EG) and trade (TO), financial development (FD) and innovation for developing nations. A negative and significant relationship with innovation. Thus, it implies that economic growth (EG) boosts through trade (TO) and financial development (FD) in developed nations while economic growth (EG) boosts through trade (TO), innovation, and financial development (FD) in developing nations. On further employing the vector error correction model, the presence of short-run causality between growth, trade and innovation in developed nations and short term causality only between growth and trade for developing nations further reaffirms the results obtained. Thus, the consistent result across various estimation techniques indicates an insignificant relationship between growth and financial development for developed nations but a significant relationship in developing countries between growth, trade, financial development, and innovation. The implications of the study highlight that in developing nations, to innovate and enhance trade and growth, policies to boost infrastructure for R&D should be implemented, while for developed nations, trade is required to boost financial strength and this growth of the economy in both the long and short run.
Keywords: Financial development; Economic growth; Innovation; Trade; VECM